Experimental evaluation and efficiency optimisation of a grid-connected converter for household energy storage applications - Kulsangcharoen, P.; Asher, G.; Rashed, M.; Klumpner, C.; Patel, C.; De, D. (2014)
This paper presents the design and the experimental evaluation of a power converter for energy storage applications suitable for household installation or to facilitate distributed energy storage capability within a local/community low-voltage grid. The technology to build the power converter is a common / low cost one in order to make it affordable which was expected to limit the overall efficiency of the energy storage system. This is why an investigation into power losses at component level followed by an efficiency optimisation procedure is developed which is confirmed by actual power loss measurements. The experimental evaluation includes also the assessment of the AC grid current quality and transient performance.